PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DI PT PERMODALAN NASIONAL MADANI (PERSERO) CABANG CISAAT KABUPATEN SUKABUMI SAAT PANDEMI - Dwi Rachmawati; Yuni Pambreni; Salma Dwi Rachmawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Quality Service is an act or act of a person or organization to provide satisfaction to customers or fellow employees. This study aims to determine the effect of service on customer satisfaction in PT Permodalan Nasional Madani. The sampling technique and this research used the Probability Sampling technique with the Slovin formula, so that the number of samples in this study amounted to 97 people with a population of 3665. The data used are primary data, namely in the form of a questionnaire. The instrument test carried out in this study was a validity test and a reliability test, the data analysis test used in testing the hypothesis in this study used correlation analysis, coefficient of determination and regression analysis using SPSS as analysis tool. The results of this study indicate a significant effect of service influence on customer satisfaction at PT Permodalan Nasional Madani.